Data-center expansion and the dynamic regional redistribution of the water-energy-food stress in Texas - Rashed Albatayneh (Resources, Conservation and Recycling, 2027)

Integrating Health in the Water-Energy-Food Nexus: A Comprehensive Review of Interdependencies, Challenges, and Future Research Opportunities - Rashed Albatayneh; Rabi Mohtar; Zainab Ashkanani; Bassel Daher; Wael K. Al-Delaimy (Current Environmental Health Reports, 2025)
Purpose of Review The Water-Energy-Food (WEF) Nexus has become a crucial framework for understanding resource interdependencies, nevertheless its integration with health remains underexplored. This review paper examines the current literature in the Water Energy Food Health (WEFH) Nexus, emphasizing the complex relationships between resource security and public health outcomes. Through a systematic literature review, the existing research trends, methodological approaches, and regional disparities in WEFH studies are analyzed. Recent Findings While health is an inherent component of resource systems, it is often treated as an externality rather than a central determinant. The review revealed that out of 1175 research articles screened, only 21 discussed WEFH as an integrated nexus. Hence, there is a crucial need for a comprehensive Water, Energy, Food, and Health research. Summary The paper proposes a conceptual WEFH integration that positions health as both an outcome and a driver of sustainable resource management based on epidemiological evidence. By analyzing health metrics implicit to the WEF nexus, the study provides insights for researchers and policymakers seeking to develop holistic strategies for resilience and equity in resource governance.